Академіки-літератори – культуротворці та мовотворці - Мех, Н. (Культура слова, 2018)
У контексті 100-ччя НАН України нам видається потрібним
звернути особливу увагу на мовотворчість академіків-літераторів
Павла Тичини, Максима Рильського, Олеся Гончара, Михайла
Стельмаха. Вони жили і творили в дуже непростий для українства
час, проте змогли сказати своєю творчістю так багато… Змогли
сказати те, що вплинуло на формування прийдешніх поколінь…
Кожен про своє… Але так, що їх почули…
Академіки-літератори є культуротворцями та мовотворцями.
Вони давали та продовжують давати можливість науковій та
культурній спільноті розширювати горизонти свого пізнання і,
водночас, спонукали та продовжують спонукати своєю науковою
та літературною творчістю до занурення у глибини нашої історії
та культури. It seems to us, in the context of the 100 th anniversary of the National
Academy of Sciences of Ukraine, to pay particular attention to the literary
work of academicians-writers Pavlo Tychyna, Maksym Rylskyi, Oles
Honchar, Mykhailo Stelmakh. They lived and worked in a very difficult time
for Ukrainians, but they were able to say so much about their creativity...
They could say what influenced the formation of future generations...
Everyone about his... But so that they were heard...
Academic writers are cultural co-authors and linguists. They gave and
continued to enable the scientific and cultural community to expand the
existing horizons of their knowledge and, at the same time, prompted and
continue to induce their scientific and literary creativity to immersion in
the depths of our history and culture.